Adnominal possessive constructions in Mordvin, Mari and Permic - Polina Pleshak (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2018)
This paper deals with adnominal possessive constructions in Moksha, Erzya, Meadow Mari, Hill Mari, Izhma Komi and Udmurt. The two main constructions that encode possessive relations in all the languages of the sample are the same: Dependentmarking and Double-marking. Izhma Komi also uses Head-marking and Juxtaposition. However, a more fine-grained analysis helps to find out many differences between the languages of the sample. Firstly, restrictions on the use of the genitive case and possessive markers can be slightly different in these languages. Secondly, there are factors that influence marking of NP elements (both the Head and the Dependent) in different ways. These factors are semantic relations, animacy hierarchy and syntactic function of an NP.